Development of a non-isothermal method for determination of diffusional parameters - Moreira, Lília A. (2011)
A non-isothermal method for determination of diffusional parameters was developed. The dependence of diffusivity on temperature was described by an Arrhenius type equation, 'with the pre-exponential factor and the,activation energy as parameters. These parameters were obtained by optimization of the fit between experimental and theoretical values, using the Simplex method of minimization. Equilibrium conditions were described with a constant unit partition coefficient. This model was applied to the diffusion of acetic acid into turnips. Results compared well with values obtained with the conventional method, using a set of experiments at isothermal conditions. The non-isothermal method has significant advantages, nameiy the need for much less experimental data and better insight into the statistical significance of the results.